Development of the kinaesthetic channel in tennis training - Segal, F. (Medicine and Science in Tennis, 2003)
A tennis player's degree of development is shown by his ability to establish patterns (tactical, technical, physical, biomechanical and mental) that can resolve as many variables of plays and throws as possible in his or her performance, effectively and efficiency. The player inputs the information through three channels: the visual channel (generally the most frequently-used channel from the start, in both instruction and training), the auditive channel (hearing the acoustic rhythm generated by the stroke and the bouncing of the ball) and the kinaesthetic channel (through the sensitivity of touch in the corporal aspect, in the transmission of the stroke through the hand, and in the position of the body, with sense stimuli transmitted by the body and the support of the feet.